A novel loss-of-function mutation in LACC1 underlies hereditary juvenile arthritis with extended intra-familial phenotypic heterogeneity - Butbul Aviel, Yonatan; Ofir, Ayala; Ben-Izhak, Ofer; Vlodavsky, Euvgeni; Karbian, Netanel; Brik, Riva; Mevorach, Dror; Magen, Daniella (Rheumatology (Oxford, England), 2021)
Abstract Objective To investigate phenotypic and molecular characteristics of a consanguineous family with autosomal-recessive, polyarticular, juvenile isiopathic arthriris (JIA) with extra-articular manifestations, including renal amyloidosis and Crohn’s disease, associated with a novel homozygous truncating variant in LACC1. Methods Whole exome sequencing (WES) or targeted Sanger verification were performed in 15 participants. LACC1 expression and cytokine array were analysed in patient-derived and CRISPR/Cas9-generated LACC1-knockout macrophages (Mϕ). Results A homozygous truncating variant (p.Glu348Ter) in LACC1 was identified in three affected and one asymptomatic family member, and predicted harmful by causing premature stop of the LACC1 protein sequences, and by absence from ethnically-matched controls and public variation databases. Expression studies in patient-derived macrophages (Mϕ) showed no endogenous p.Glu348Ter-LACC1 RNA transcription or protein expression, compatible with nonsense-mediated mRNA decay. WES analysis in the asymptomatic homozygous subject for p. Glu348Ter-LACC1 detected an exclusive heterozygous variant (p.Arg928Gln) in complement component C5. Further complement activity analysis suggested a protective role for the p.Arg928Gln-C5 variant as a phenotypic modifier of LACC1-associated disease. Finally, cytokine profile analysis indicated increased levels of pro-inflammatory cytokines in LACC1-disrupted as compared with wild-type Mϕ. Conclusions Our findings reinforce the role of LACC1 disruption in autosomal-recessive JIA, extend the clinical spectrum and intra-familial heterogeneity of the disease-associated phenotype, indicate a modulatory effect of complement factor C5 on phenotypic severity, and suggest an inhibitory role for wild-type LACC1 on pro-inflammatory pathways.